Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai pada Dinas Sosial Kota Ambon - Papalia, Tri Irmayuni Kalsum; soselisa, pieter sammy; Rahanra, Ivonny Yeany; Patty, Julia Theresia (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to determine the effect of supervision and work discipline on employee productivity at the Social Service Office in Ambon City. This research uses a quantitative method with a descriptive approach. Data was collected through questionnaires distributed to 35 respondents working at the Social Service Office in Ambon City. Data analysis techniques used include validity tests, reliability tests, and multiple linear regression analysis. The results indicate that supervision has a positive and significant effect on employee productivity. In addition, work discipline also significantly influences employee productivity. Therefore, it can be concluded that good supervision and a high level of work discipline can improve employee productivity at the Social Service Office in Ambon City. This study provides important implications for organizations to pay attention to effective supervision and efforts to enhance work discipline to improve employee productivity.